Data acquisition using the IBM PC / Teratai @ Zainab Leman and Salmiah Wahid - Leman, Teratai @ Zainab; Wahid, Salmiah (1989)
Data acquisition is a restricted kind of data collection. It is of interest mainly to scientists and engineers. There are two distinguishing features. First, the information we wish to acquire is contained in physical variables, such as temperature, velocity and electric current.